The Role of Spiritual Value-Based Sharia Marketing in Facing the Dislocation of the Traditional Culinary Identity of Dawet Ayu Pandansari - Vivin Aminah Nur Afidah; Kadenun Kadenun; Khoirul Fathoni (JURNAL ECONOMINA, 2026)
The growth of halal culinary and changes in consumer behavior require businesses to combine profit with spiritual and cultural values. Amid the onslaught of modern beverages, traditional culinary delights risk losing their identity. This study aims to analyze the sharia marketing strategy of Dawet Ayu Pandansari and its supporting and inhibiting factors. Using a descriptive qualitative approach, data was collected through interviews, observation, and documentation. The results indicate a strategy based on the principles of divinity, ethics, reality, and humanity, centered on honesty, natural quality, and humane service. Halal awareness and trust support success, while competition and limited digital promotion pose obstacles. This strategy effectively maintains identity, strengthens competitiveness, and preserves culinary heritage.